College Student Allocation System / Asmahani Mohd Zin - Mohd Zin, Asmahani (Faculty of Computer and Mathematical Sciences, 2007)
This research project is about developing College Student Allocation System using Wampserver and web application framework in UiTM. The objectives of this research are to identify all the requirement specification of College Student Allocation System (CSAS), to model the design of College Student Allocation System (CSAS) based on requirement specification and to develop the prototype of the College Student Allocation System adopting web application framework that is Mamboserver. The researcher gets the data collection from tfie interview and questionnaire to gather all the requirement that are needed in this research said prove the findings at the end of the reseeu'ch. In the end of research project period, researcher found that the result is complying with the objectives and therefore all the objectives in this research project have been achieved.